Dementia prevention through the eyes of individuals at risk: insights from a satisfaction survey within the programme for dementia prevention in Luxembourg - Erz, Dorothee; Schröder, Valerie E.; Skrozić, Amna; Loureiro, João M.; Possemis, Nina; Krüger, Rejko (Frontiers in Aging, 2026)
IntroductionEstablishing a nationwide prevention programme can be challenging, particularly in the field of dementia, as role model projects are lacking, and the topic is still associated with stigma. Hence, a satisfaction survey for the programme dementia prevention (pdp) in Luxembourg was conducted to obtain direct feedback from the participants on how the programme and its multidomain interventions are accepted and evaluated.MethodsIn 2023 and 2024, a satisfaction survey was sent out to all eligible pdp participants (n = 575). Participation was voluntary and anonymous, and the survey could be completed in paper form or online. The questionnaire contained 12 closed-ended questions rated on a Likert-scale and 3 open questions.Results302 (52.5%) participants returned the survey. The analysis revealed a high level of satisfaction with an overall average satisfaction of 4.7/5 points (SD = 0.6). 281 participants (95.9%) would recommend the pdp to others. A breakdown of the statements provided insights into areas of interest from the participants’ perspective.DiscussionOur study shows that the pdp is well received by its participants, underlined by a high level of satisfaction and positive responses to what pdp offers. Findings showed that interactions were perceived as informative to gain insights into one’s own cognitive performance and raised awareness of possibilities to reduce dementia risk, i.e., via lifestyle changes. Our results can serve as orientation for the implementation of emerging prevention programmes in different healthcare settings.